Thermal management of electronics devices with PCMs filled pin-fin heat sinks: A comparison - Ali, Hafiz Muhammad; Arshad, Adeel; Jabbal, Mark; Verdin, Patrick G. (Elsevier, 2017)
The present paper covers the comparison of two different configurations (square and circular) pin-fin heat sinks embedded with two different phase change materials (PCMs) namely paraffin wax and n-eicosane having different thermo-physical properties were carried out for passive cooling of electronic devices. The pin-fins, acting as thermal conductivity enhancers (TCEs), of 2mm square and 3mm circular fin thickness of constant volume fraction of 9% are chosen and input heat fluxes from 1.2kW/m2 to 3.2kW/m2 with an increment of 0.4kW/m2 are provided. Two different critical set point temperatures (SPTs) 45°C and 65°C are chosen to explore the thermal performance in terms of enhancement ratios, enhancement in operation time, latent heating phase duration, thermal capacity and conductance. The results show that 3mm diameter of circular pin-fins has the best thermal performance in passive thermal management of electronic devices.
Keywords: Phase change materials (PCMs); Thermal conductivity enhancers (TCEs); Pin-fin heat sinks; Paraffin wax; n-Eicosane; Set point temperatures (SPTs)